Escribir con voz de niño la guerra civil española : representaciones de la infancia en novelas juveniles actuales sobre la Guerra Civil Española - Reyva Franco (Amnis)
In the literature for young people, the relationship between truth and fiction is essential and exposes the possibility and the challenge of finding new strategies that allow for a plausible narrative from the voice of childhood, generally embodied in the main character of the story. In this article the central proposal is framed in the perspective of the Spanish civil war from different points of view and, with it, a historical recognition of the daily and minimal life through the vision of each personage. One of the coordinates of this article is based on the idea that a story is always historical, the reason lies not only in the facts it narrates but because the author can’t escape the details and conditions of his own time, in works. Chosen in a wide bibliography related to the theme of the Spanish Civil War, which also have in common the narrative work of the small stories, the intimacy of the children's characters and the way of assuming their daily life.